M2 Macrophages Mediate the Resistance of Gastric Adenocarcinoma Cells to 5-Fluorouracil through the Expression of Integrin β3, Focal Adhesion Kinase, and Cofilin - Daniel Ngabire; Irvine Niyonizigiye; Maheshkumar Prakash Patil; Yeong-Ae Seong; Yong Bae Seo; Gun-Do Kim (Journal of Immunology Research)
Tumor microenvironment components dictate the growth and progression of various cancers. Tumor-associated macrophages are the most predominant cells in TME and play a major role in cancer invasiveness. Gastric cancer is one of the most common cancers in Asia, and recently, various cases of resistance to fluorouracil treatment have been reported. In this study, we investigated the role of alternatively activated macrophages in the resistance of AGS gastric cancer cells to fluorouracil. THP-1 cells were polarized using recombinant human IL-4, then were cocultured with AGS cells treated with fluorouracil. Cell viability, Western blot, immunofluorescence, and cell invasion were performed for this investigation. Our results demonstrated that polarized macrophages initiated the survival of treated AGS cells and induced the resistance in AGS by upregulating the expression of integrin β3, focal adhesion protein (FAK), and cofilin proteins. These results reveal that integrin β3, focal adhesion protein (FAK), and cofilin proteins are potential targets for the improvement of fluorouracil efficacy in gastric cancer treatment.